Sick sinus syndrome associated with anti-programmed cell death-1. Issue 1 (16th July 2018) - Hsu, Chien-Yi; Su, Yu-Wen; Chen, San-Chi
Abstract : Background: Use of anti-programmed cell death-1 (anti-PD-1) has been successful in treating many types of cancers. Despite its promising efficacy, immune-related adverse events are still a major concern. Immune-related cardiotoxicity, which is rare but fatal, has recently become a focus of attention. Cardiotoxicities including myocarditis, cardiomyopathy, cardiac fibrosis, heart block and cardiac arrest have been reported. Of these toxicities, myocarditis is often accompanied by dysrhythmia. The presentation of sick sinus syndrome as an immune-related adverse event has not yet been reported. Here, we reported the first case of sick sinus syndrome, a rare toxicity induced by anti-PD-1. Case presentation: A 42-year-old male patient who had metastatic hepatocellular carcinoma failed treatment with sorafenib. Pembrolizumab at a fixed dose of 100 mg every three weeks was given. His heart rate gradually slowed down and he presented sick sinus syndrome with a lowest heart rate of 38 bpm after six cycles of pembrolizumab. He denied chest tightness, cold sweating, palpitation and dyspnea. Lab data including cardiac enzyme, electrolytes and thyroid function were all within a normal range. Simultaneously, he complained of fatigue, dizziness and anorexia with hypotension. Lab data revealed low cortisol and ACTH levels. Anti-PD-1 induced adrenal insufficiency was suspected. Low-dose cortisone (12.5 mg) was prescribed, and the patient's symptoms, hypotension and sick sinus syndrome showed rapid improvement. Cortisone was gradually titrated and discontinued three weeks later. His sick sinus syndrome did not relapse and the cortisol and ACTH level returned to normal. Conclusions: Sick sinus syndrome caused by anti-PD-1 treatment is a rare adverse event. With the development of sick sinus syndrome, myocarditis should be the first differential diagnosis because of its lethality. From this case, we learned that sick sinus syndrome may be a presentation of immune- or adrenal insufficiency-mediated sinus node dysfunction, both could be reversed with a glucocorticoid supplement.